Pelaksanaan Pembinaan Narapidana Menurut Undang Undang Nomor 12 Tahun 1995 Tentang Pemasyarakatan Untuk Mencegah Pengulangan Tindak Pidana (Studi Di Lembaga Pemasyarakatan Kelas II A Pematang Siantar) - Rudi Fernando Sianturi (Universitas Islam Sumatera Utara, 2022)
He main purpose of the Correctional Institution is to provide guidance for inmates based on the institutional system, and the method of coaching as the final part of the criminal justice system and criminal justice system.In the formulation of Article 1 number 1 of Law Number 12 of 1995 concerning Corrections, it is explained that